Editorial: scoring systems in primary biliary cholangitis – time to make a move. Authors' reply. Issue 8 (21st March 2017) - Yang, F.; Yang, Y.; Tang, R.; Gershwin, M. E.; Ma, X.
Abstract : Linked Content This article is linked to Mells and Jones and Yang et al papers. To view these articles visithttps://doi.org/10.1111/apt.13984 andhttps://doi.org/10.1111/apt.13927 .